Involvement of AoMdr1 in the Regulation of the Fluconazole Resistance, Mycelial Fusion, Conidiation, and Trap Formation of Arthrobotrys oligospora - Yankun Liu; Xuewei Yang; Meichen Zhu; Na Bai; Wenjie Wang; Jinkui Yang (Microorganisms, 2023)
Multidrug resistance (Mdr) proteins are critical proteins for maintenance of drug resistance in fungi. Mdr1 has been extensively studied in Candida albicans; its role in other fungi is largely unknown. In this study, we identified a homologous protein of Mdr (AoMdr1) in the nematode-trapping (NT) fungus Arthrobotrys oligospora. It was found that the deletion of Aomdr1 resulted in a significant reduction in the number of hyphal septa and nuclei as well as increased sensitivity to fluconazole and resistance to hyperosmotic stress and SDS. The deletion of Aomdr1 also led to a remarkable increase in the numbers of traps and mycelial loops in the traps. Notably, AoMdr1 was able to regulate mycelial fusion under low-nutrient conditions, but not under nutrient-rich conditions. AoMdr1 was also involved in secondary metabolism, and its deletion caused an increase in arthrobotrisins (specific compounds produced by NT fungi). These results suggest that AoMdr1 plays a crucial role in the fluconazole resistance, mycelial fusion, conidiation, trap formation, and secondary metabolism of A. oligospora. Our study contributes to the understanding of the critical role of Mdr proteins in mycelial growth and the development of NT fungi.